Population of the world and regions as the principal energy consumer; International Journal of Energy Economics and Policy; Vol 8, iss. 3 - Lizunkov V. G. Vladislav Gennadyevich; Politsinskaya E. V. Ekaterina Viktorovna; Malushko E. Yu. Elena Yurjevna; Kindaev A. Yu. Andrey Yurjevich; Minin M. G. Mikhail Grigoryevich (2018, 2018)
Title screen